Improvement of Growth and Yield of Romaine Lettuce (Lactuca sativa L.) with the Application of Liquid Organic Fertilizer from Goat Manure and a Combination of Biochar Charcoal as Planting Media - Afdil Arfadillah Putra Diwa; Andriani Eko Prihatiningrum (Demeter: Journal of Farming and Agriculture, 2025)
This study aims to re-examine the optimization of Romaine lettuce yield under the application of a combination of biochar charcoal husk growing media and goat manure liquid organic fertilizer. This study was conducted from July to September 2024 at an experimental site located in Tebel Barat Village, Gedangan Subdistrict, Sidoarjo Regency, at an altitude of approximately 25 meters above sea level. This area has a temperature range of 21-34°C and an average rainfall of 1,300-1,700 mm per year. This study used a randomized block design with two treatment factors. The first factor involved the application of planting media consisting of three levels, namely 0g of biochar from rice husk charcoal, 29g of biochar from rice husk charcoal. Biochar Rice Husk Charcoal 147g. The second factor is the concentration of goat manure POC with 3 levels, namely: Liquid Organic Fertilizer from Goat Manure 1ml/5lt Water, Liquid Organic Fertilizer from Goat Manure 3ml/5lt Water, Liquid Organic Fertilizer from Goat Manure 5ml/5lt Water. The treatment was repeated three times, resulting in 27 experimental units. Data analysis was performed using analysis of variance, followed by a 5% BNJ test with observation variables including plant height, number of leaves, root length, wet weight, dry weight, and harvest index. The biochar husk charcoal growing medium treatment showed significantly different results in observation variables such as plant height and root length. In the plant height observation, the highest result was found in the observation without biochar charcoal husks. And in the root length observation variable, the highest value was found in the concentration without biochar charcoal husks. Meanwhile, the goat manure POC fertilizer observation results showed significant differences in several observation variables, such as plant height and number of leaves. Plant height showed significant results at 7, 14, and 35 days after planting, with the highest results for goat manure POC at 5 ml/5 L of water at 7 days after planting, goat manure POC at 5 ml/5 L of water at 14 days after planting, and goat manure POC at 1 ml/5 L of water at 35 days after planting. In the leaf number observation variable, the highest value was obtained in the treatment with 5 ml/5 L of goat manure POC. The biochar charcoal husk growing medium, observed without biochar charcoal husk and goat manure POC fertilizer at a dose of 5ml goat POC and 5L water, was able to produce the best vegetative growth on lowland plantations with good soil conditions, showing potential for further application in the future.